Pemanfaatan Penerapan Media Berbasis Software Anates pada Mata Kuliah Evaluasi Pembelajaran di Universitas Batanghari Jambi - Pratiwi Indah Sari; Redi Indra Yudha (Universitas Batanghari Jambi, 2020)
This study aims to determine the use of Anates software based media in learning evaluation courses at Batanghari University, Jambi. The design of this study uses descriptive qualitative. Meanwhile, the technique in this study uses a purposive technique that is the determination of informants not based on guidelines or based on population representation, but based on the depth of information needed related to the research problem. The results showed that there was an influence between the application of the use of Anates software-based applications in the learning evaluation course with the item analysis material at Batanghari University, Jambi. Thus, the use of media in lectures is very helpful for students to be able to understand new knowledge and insights that are not only limited to theory, but rather to practice to support the theories they learn.